1997
DOI: 10.2307/2265990
|View full text |Cite
|
Sign up to set email alerts
|

Response of an Insect Predator to Prey Fed Multiple Allelochemicals Under Representative Thermal Regimes

Abstract: We examined the effects of three allelochemicals found in tomato (chlorogenic acid, rutin, and tomatine) and two thermal regimes (21Њ:10ЊC and 26Њ:15ЊC, representing spring and summer, respectively) on the performance of a generalist insect predator (Podisus maculiventris: Pentatomidae) fed prey containing those allelochemicals. The prey were Manduca sexta (Sphingidae) caterpillars, Solanaceae specialists with a preference for tomato. Whether an allelochemical had a negative, neutral, or positive effect on dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 56 publications
(86 reference statements)
1
9
0
3
Order By: Relevance
“…3) showing that it varies with prey type and nutritional quality, as found for Podisus maculiventris by De Clercq et al (1998), suggesting that food quality can be more important than its quantity. This was also found by Stamp et al (1997) who showed that food quality can interfere with the feeding period and survival rate of Pentatomidae predators. Thus, it appears that M. domestica larvae have lower nutritive quality than other prey.…”
Section: Resultssupporting
confidence: 66%
“…3) showing that it varies with prey type and nutritional quality, as found for Podisus maculiventris by De Clercq et al (1998), suggesting that food quality can be more important than its quantity. This was also found by Stamp et al (1997) who showed that food quality can interfere with the feeding period and survival rate of Pentatomidae predators. Thus, it appears that M. domestica larvae have lower nutritive quality than other prey.…”
Section: Resultssupporting
confidence: 66%
“…Adding further allelochemical dimensions is an important aim Osier 1998, Nelson andKursar 1999), as is varying abiotic factors such as temperature (Stamp 1990, Stamp and Horwath 1992, Stamp and Yang 1996. Higher level trophic effects could also be considered (Stamp et al 1997).…”
Section: Resultsmentioning
confidence: 99%
“…However, relatively few studies have examined the effects on predator growth of ingesting prey containing allelochemicals. Usually the effects were negative (Paradise & Stamp, 1990, 1993Stamp et al, 1991;Bozer et al, 1996;Traugott & Stamp, 1997), but not in all cases (Osier et al, 1996;Stamp et al, 1997). Secondly, studies on the effects of diet breadth of herbivorous prey have not contrasted the effects of specialist vs. generalist herbivores feeding on the same plant species.…”
Section: Introductionmentioning
confidence: 99%